PENGARUH BAURAN PROMOSI, KUALITAS PELAYANAN, DAN CITRA PERUSAHAAN TERHADAP KEPUASAN JAMAAH UMROH AL-SHAHBA MALANG MELALUI KEPERCAYAAN JAMAAH SEBAGAI VARIABEL INTERVENING - Anggraini, Maulidia Wulan; Karnawati, Tin Agustina; Ruspitasari, Widi Dewi (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2020)
The purpose of the research is to determine the effect of the promotion mix, service quality, and company image toward satisfaction of Al-Shahba Malang pilgrims through the pilgrims’ trust as an intervening variable. Population of this research is based on consumer who choosing and using Al-Shahba Malang’s umrah package in 2016-2018 as many 276 people. Sample used in this research covers 163 consumer using purposive sampling technique. In this research, the data collection techniques is by questionnaires, interviews, observations, and documentations. The data gained from questionnaires was analyzed by using instrument test, path analysis, hypoteshis testing and the coefficient of determination with SPSS 21.0 version. The research proves that the three independent variables : promotion mix, service quality, and corporate image, has a positive and significant influence on the pilgrims’ trust. The promotion mix, service quality, and corporate image has a positive and significant influence on the pilgrims’ satisfaction. The pilgrims’ trust has a positive and significant influence on the pilgrims’ satisfaction. And the promotion mix, service quality, corporate image has a positive and significant indirect influence on the pilgrims’ satisfaction through pilgrims’ trust as an intervening variable.